High expression of S100P is associated with unfavorable prognosis and tumor progression in patients with epithelial ovarian cancer - Wang, Xiangyu (Am J Cancer Res, 2015)
Accumulating evidence has demonstrated that S100P is involved in the tumorigenesis and progression of multiple cancers. In the current study, we evaluated the expression of S100P in epithelial ovarian cancer and assessed its relevance to clinicopathological characteristics. Moreover, we investigated the biological effects of S100P using A2780 and SKOV3 cells. S100P expression was significantly increased in epithelial ovarian cancer specimens compared with fallopian tube tissues and normal ovary tissues. And high expression of S100P in epithelial ovarian cancer samples was significantly associated with tumor stage (P<0.001), serum CA125 level (P=0.026), residual tumor (P<0.001), ascites (P<0.001) and lymph nodes metastasis (P<0.001). Multivariate Cox analysis showed that S100P expression was an independent prognostic factor of overall survival (OS) and progression free survival (PFS) (P=0.017 and 0.031, respectively). Functional assays showed that overexpression of S100P promoted cell proliferation and cell cycle progression but did not affect cell migration and invasion in A2780 and SKOV3 cells. These data suggest that S100P may contribute to tumor development in epithelial ovarian cancer and could be a useful marker for the prognosis of epithelial ovarian cancer patients.